Simulation of rigidly-linked nanosatellites - Lecuyot, Arnaud; Hobbs, Stephen; Honstvet, Ian (Cranfield University, 2004)
Rigidly linked nanosatellites are simulated as part of a PhD research on a new concept of space structure. Applications include a 1D interferometer in Earth and Lagrange orbits and a 3D Solar concentrator in Earth and Moon orbit. Simulation methods include a link tension derivation based on tether dynamics, and a simple On-Off constant thrust nanosatellite controller. Results show the basic controllability of most proposed applications. At system design level, the controller does not provide adequate lifetime in its current form, but the concept is in principle feasible.